Natural theology and religious belief - Baker-Hytch, M (Cambridge University Press, 2023)
It is no exaggeration to say that there has been an explosion of activity in the field of philosophical enquiry known as natural theology. Having been smothered in the early part of the twentieth century due to the dominance of logical positivism, natural theology began to make a comeback in the late 1950s as logical positivism collapsed and analytic philosophers took a newfound interest in metaphysical topics such as possibility and necessity, causation, time, the mind–body problem, and God. This chapter begins by considering how we might characterize natural theology as a field of enquiry. It then proceeds to survey the landscape of contemporary natural theology, which has spawned a large and at times highly technical body of literature. Finally, consideration is given to two epistemological issues confronting the theist who wishes to appeal to natural theology, namely, the problem of the gap(s) and the problem of accessibility.